FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI - Irene, Irene; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to obtain empirical evidence about the effect of profitability, leverage, security, and auditor reputation on bond rating in non financial companies listed on the Indonesia Stock Exchange for the period of 2016 to 2018. This research uses purposive sampling method. Samples were taken from 30 non financial companies with a total of 90 data for three years. Data processed with SPSS 25. Hypothesis testing in this study using logistic regression analysis. The result on this study shows that profitability has positive effect on bond rating, while leverage, security, and auditor reputation have no effect on bond rating.